The arithmetic mean, geometric mean, and harmonic mean of a , b , c are 8, 5, 3, respectively. What is the value of a 2 + b 2 + c 2 ?
This problem is posed by Matt .
Details and Assumptions:
The arithmetic mean, geometric mean, and harmonic mean of n numbers a 1 , a 2 , … , a n are (respectively)
n ∑ i = 1 n a n , n i = 1 ∏ n a n , ( ∑ i = 1 n a n 1 n ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
From the problem we knew that:
3 a + b + c = 8
3 a b c = 5
a 1 + b 1 + c 1 3 = 3
Arrange them we get:
( 1 ) : a + b + c = 2 4
( 2 ) : a b c = 1 2 5
( 3 ) : a 1 + b 1 + c 1 = 1
a b c a b + b c + a c = 1
a b + b c + a c = 1 2 5
Next,
a 2 + b 2 + c 2
= ( a + b + c ) 2 − 2 ( a b + b c + a c )
= 2 4 2 − 2 ( 1 2 5 )
= 3 2 6
Nice solution @Christopher Boo
Arithmetic Mean = 3 a + b + c = 8 Hence, ( a + b + c ) = 2 4 .
Geometric Mean = ( a b c ) 1 / 3 = 5 . then, a b c = 1 2 5 .
Harmonic Mean = a 1 + b 1 + c 1 3 = 3 o r , a 1 + b 1 + c 1 = 1 o r , a b + b c + a c a b c = 1 o r , a b + b c + a c = a b c = 1 2 5
We know that, a 2 + b 2 + c 2 = ( a + b + c ) 2 − 2 ( a b + a c + b c ) = 2 4 2 − 2 × 1 2 5 = 5 7 6 − 2 5 0 = 3 2 6
(a +b+c)/3 =8
thus a+b+c =24
(abc)^1/3 =5
abc=125
3/(1/a +1/b+1/c) =3
hence abc= ab+bc+ca
(a+b+c)^2 =a^2 +b^2 +c^3 +2(ab +bc+ca)
substituting all given values
a^2+b^2+c^2=326
arithmetic mean=8= (a+b+c)/3
a+b+c=8x3=24
geometric mean=5=cube root of (abc)
abc=5^3=125
harmonic mean=3=3/[(1/a)+(1/b)+(1/c)]
(1/a)+(1/b)+(1/c)=3/3=1
(bc+ac+ab)/abc = 1
(bc+ac+ab)/125=1
(bc+ac+ab)=125
(a+b+c)^2=a^2+b^2+c^2+2(ab+bc+ca)
a^2+b^2+c^2=(a+b+c)^2-2(ab+bc+ca)=24^2-2(125)=326
a+b+c=(8 3)=24 abc=125 1/a+1/b+1/c=3 1/3=1 ab+bc+ca=125 a^2+b^2+c^2=(a+b+c)^2-2(ab+bc+ca)
The conditions in the problem can be written as a + b + c = 2 4 , a b c = 1 2 5 , a 1 + b 1 + c 1 = 1 . The third equation also can be written as a b c a b + b c + c a = 1 . By the second equation, a b + b c + c a = 1 2 5 . Square the first equation, we get a 2 + b 2 + c 2 + 2 a b + 2 b c + 2 c a = 5 7 6 , a 2 + b 2 + c 2 = 3 2 6 .
Problem Loading...
Note Loading...
Set Loading...
From the definitions of the three means, we can rewrite the three statements in the following ways.
1: a + b + c = 2 4
2: a b c = 1 2 5
3: a b + b c + a c 3 a b c = 3
Substituting the second eq. into the third one, we get that
a b + b c + a c = 1 2 5
By squaring the first equation, we get the following:
a 2 + b 2 + c 2 + 2 ( a b + b c + a c ) = 5 7 6
Now, we can isolate for a 2 + b 2 + c 2 by putting in what we know.
a 2 + b 2 + c 2 = 5 7 6 − 2 ( 1 2 5 )
a 2 + b 2 + c 2 = 3 2 6